2019
DOI: 10.1177/0020764019827986
|View full text |Cite
|
Sign up to set email alerts
|

Attempting to disentangle the relationship between impulsivity and longitudinal self-harm: Epidemiological analysis of UK household survey data

Abstract: Background Impulsivity may be an important risk factor in terms of future self-harm. However, the extent of this, whether it may relate to self-harm that is new in onset and / or repetition of self-harm, and the detail of any interaction with mood instability and childhood sexual abuse requires detailed examination. Aims We used the 2000 Adult Psychiatry Morbidity Survey and 18-month follow-up data to test hypotheses relating to the role of impulsivity, childhood sexual abuse (CSA), and mood instability (MI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This pattern was consistent across 2007 and 2014 datasets, but the effect was lower overall in 2014. The consistently lower impact of impulsivity as a mediator for both thoughts and attempts is interesting: it may indicate that mood instability itself includes important elements of impulsivity ( de Cates et al, 2019 ). As might be expected, we also confirmed that depression was an important mediator for suicide attempts and thoughts in persecutory ideation and auditory hallucinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern was consistent across 2007 and 2014 datasets, but the effect was lower overall in 2014. The consistently lower impact of impulsivity as a mediator for both thoughts and attempts is interesting: it may indicate that mood instability itself includes important elements of impulsivity ( de Cates et al, 2019 ). As might be expected, we also confirmed that depression was an important mediator for suicide attempts and thoughts in persecutory ideation and auditory hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…Such self-harm has also been linked to impulsivity, which may also be a mediator of longer-term clinical outcome ( Nanda et al, 2016 ). Mood instability and impulsivity have a complex relationship, particularly as potential mediators of self-harm ( de Cates et al, 2019 ). Previous work using community data has identified that psychotic symptoms are associated with self-harm risk, and that this relationship is not necessarily explained by symptoms of borderline personality disorder (which include impulsivity and mood instability) ( Kelleher et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Self-harm is the result of complex interactions of personality factors, including impulsivity, social factors and mental state. 46 It is well established that impulsivity is an important risk factor for suicide attempts. 47 It has been shown that impulsivity increases with exposure to nicotine, returns to a normal levels with abstinence and increases with re-challenge after abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Self-harm is the result of complex interactions of personality factors, including impulsivity, social factors and mental state 47 . It is well established that impulsivity is an important risk factor for suicidal attempts 48 .…”
Section: Discussionmentioning
confidence: 99%